Education of Bullying Behavior in Adolescents Throungh the "Old School" Program (Do Not Have Bullying Between Us) - St. Hateriah*; Sarkiah Sarkiah (Riwayat: Educational Journal of History and Humanities, 2023)
In recent years, the number of cases of bullying has increased, both by reenagers at the junior high and high school levels. In Indonesia, there are also many cases of bullying that occur in various places. Acts of violence committed by a group of classmates, in the form of beatings, kicks and ridicule. The types of bullying that are carried out also vary, there are verbal, non-verbal, and cyber bullying. Bullying behavior develops rapidly in the school environment and often gives negative input to students, for example in the form of punisments thet are not constructive so as not to develop a sense of respect and respect among fellow school members. Some chilren engage in bullying behavior in an attempt to prove that they can belong to a certain group, even though they themselves feel uncomfortable with this behavior. Bullying that is done continuously can cause trauma, fear, depression, anxiety, and even death. Bullying can have a negative impact on both the perpetrator and the victim. Bullying can result in physical and mental health of emotional problems, inculding depressions and and anxiety, which can lead to decreased performance in school and other deviant behavior. The purpose of this community service is to provide students with an understanding of bullying behavior, forms of bullying and their impacts, so that students are able to eliminate the culture of bullying in everyday interactions.